Planck activities at MPA - Bartelmann, Matthias; Hell, Rüdiger (Mining the sky, 2003)
We summarise activities going on at the Max Planck Institut für Astrophysik (MPA) in preparation of the Planck satellite mission. There are three areas of activity, the development of an automatic process coordinator, the coordination of the development and the integration of an end-to-end data simulation pipeline, and the construction of the archive for all of Planck’s final data products.